2017
DOI: 10.1016/j.jenvrad.2016.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Radiological and material characterization of high volume fly ash concrete

Abstract: The main goal of research presented in this paper was the material and radiological characterization of high volume fly ash concrete (HVFAC) in terms of determination of natural radionuclide content and radon emanation and exhalation coefficients. All concrete samples were made with a fly ash content between 50% and 70% of the total amount of cementitious materials from one coal burning power plant in Serbia. Physical (fresh and hardened concrete density) and mechanical properties (compressive strength, splitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(17 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…The compressive strength of HVFA concrete with 50% Class C FA replacement was 22.6%, 21.7% and 18.3% less than that of ordinary concrete, respectively, for 3, 14 and 28 days curing [15]. When the curing period is 28 days, compressive strength of HVFA concrete increased by nearly 20% as the FA content increased from 50% to 70% by mass of total cementitious materials [16]. Michelle R. Nokken et al [17] found nearly 47.6% and 85.7% reduction of compressive strength, respectively, for 60% and 80% FA replacement level by mass at the curing age of 28 days.…”
Section: Early Age and Long-term Compressive Strengthmentioning
confidence: 90%
“…The compressive strength of HVFA concrete with 50% Class C FA replacement was 22.6%, 21.7% and 18.3% less than that of ordinary concrete, respectively, for 3, 14 and 28 days curing [15]. When the curing period is 28 days, compressive strength of HVFA concrete increased by nearly 20% as the FA content increased from 50% to 70% by mass of total cementitious materials [16]. Michelle R. Nokken et al [17] found nearly 47.6% and 85.7% reduction of compressive strength, respectively, for 60% and 80% FA replacement level by mass at the curing age of 28 days.…”
Section: Early Age and Long-term Compressive Strengthmentioning
confidence: 90%
“…The calculation of I-index of any raw (sand, aggregate), construction materials (cement, lime) or by-products would imply that 100% of these materials are used as building materials. Of course, this not realistic for most construction materials where only a fraction of certain by-products can be included, but it provides an opportunity for their screening or prediction [6] of the I-index of the final product. If needed, a dilution factor could be used for a given application to achieve more realistic screening (Fig.…”
Section: I-indexmentioning
confidence: 99%
“…The radionuclide content of recycled by-products cannot be ignored since they can cause increased radiological risk. According to EU-BSS [27], the dilution factor has to be determined as the function of the activity concentration of the components [6,104]. The screening of by-products and construction materials can be a practical tool to identify and manage potential material resources which can pose an elevated risk.…”
Section: Estimation Of Maximum Allowable Mixing Ratio Of By-products mentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, fly ash has been substituted for up to 30-40% of the cementitious materials in concrete mixtures [6][7][8][9]. However, when fly ash is used as an alternative to cement, the concrete's early strength is slow to develop, limiting the viability of this type of utilization [10]. Some studies have indicated that a more viable utilization of fly ash is as a substitute for the fine aggregate in concrete mixtures [4,11].…”
Section: Introductionmentioning
confidence: 99%